2019
DOI: 10.7150/ijms.32752
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Respiratory Failure in Interstitial Lung Diseases: Overview and Clinical Insights

Abstract: Interstitial lung diseases (ILDs) may be complicated by chronic respiratory failure (CRF), especially in the advanced stages. Aim of this narrative review is to evaluate the current evidence in management of CRF in ILDs. Many physiological mechanisms underlie CRF in ILDs, including lung restriction, ventilation/perfusion mismatch, impaired diffusion capacity and pulmonary vascular damage. Intermittent exertional hypoxemia is often the initial sign of CRF, evolving, as ILD progresses, into continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 166 publications
(192 reference statements)
0
24
0
1
Order By: Relevance
“…As in COPD, oxygen therapy is also instituted in most cases of patients with interstitial lung diseases (ILD) 16 , 17 . This is a group of lung diseases characterized by alveolar damage with fibroblastic and/or inflammatory proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…As in COPD, oxygen therapy is also instituted in most cases of patients with interstitial lung diseases (ILD) 16 , 17 . This is a group of lung diseases characterized by alveolar damage with fibroblastic and/or inflammatory proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with advanced disease, reducing symptoms and improving quality of life are required (Zou et al, 2020). Long-term oxygen therapy, with high flow and high concentration of oxygen, is often used to decrease dyspnea and improve exercise tolerance (Koyauchi et al, 2018;Faverio et al, 2019). It is also reported that oxygen supplementation increased exercise capacity for patients with interstitial lung diseases including IPF (Bell et al, 2017;Dowman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous PAP provides alveolar inflation and prevents atelectasis. The physiological benefits of CPAP such as stabilization of chest wall and upper airway, reduction of lung resistance and improvement of tidal volume, oxygenation, and functional residual capacity increase the success of extubation of preterm infants ( 9 ). The use of CPAP significantly reduced the need for invasive mechanical ventilation but the rates of CPAP failure are high.…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…While surfactant protein deficiency, neuroendocrine cell hyperplasia of infancy, pulmonary interstitial glycogenesis, and developmental disorders are specific to infancy, ILD related to exposure/environment insults, ILD related to systemic and immune diseases, and ILD related to primary lung parenchyma dysfunctions constitute the non-age specific group ( 88 ). Anti-inflammatory and immunosuppressive agents are the cornerstones of pharmacological therapy, while oxygen and ventilatory support are required for patients with hypoxemia and respiratory failure ( 9 ).…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation